1995
DOI: 10.1063/1.359957
|View full text |Cite
|
Sign up to set email alerts
|

Low filament temperature deposition of a-Si:H by hot-wire chemical vapor deposition

Abstract: Hydrogenated amorphous silicon, a-Si:H, is deposited from silane and hydrogen by hot-wire chemical vapor deposition using a tungsten wire filament at a temperature Tfil=1200 °C. Film properties depend on whether the films were deposited using filaments with an accumulated deposition time lower than 90 min (‘‘new’’ filaments) or longer than 90 min (‘‘old’’ filaments). The deposition rate for films deposited with ‘‘new’’ filaments is 4 times higher than that for aged filaments. For ‘‘new’’ filaments, a monotonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
9
0
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 34 publications
2
9
0
1
Order By: Relevance
“…Our present results enable now the understanding of the sharp percolation transition at low x ͑ϳ0.3͒ values that was reported for n-type 17,21,23 and p-type 26 doped materials, and the relatively high-x ͑ϳ0.7͒ percolation threshold that we 29,30 and others 4,5 found in undoped systems. According to the structural data 12 and the present detection of the conducting columnar tissue, one would expect two subsequent percolation transitions in c-Si: H; a low-x transition that is associated with conduction in a regular percolation system made of sphericallike conducting particles, 36 and another, high-x transition, that is associated with the intercolumn tissue, such as the one observed in a network of conducting sheets.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Our present results enable now the understanding of the sharp percolation transition at low x ͑ϳ0.3͒ values that was reported for n-type 17,21,23 and p-type 26 doped materials, and the relatively high-x ͑ϳ0.7͒ percolation threshold that we 29,30 and others 4,5 found in undoped systems. According to the structural data 12 and the present detection of the conducting columnar tissue, one would expect two subsequent percolation transitions in c-Si: H; a low-x transition that is associated with conduction in a regular percolation system made of sphericallike conducting particles, 36 and another, high-x transition, that is associated with the intercolumn tissue, such as the one observed in a network of conducting sheets.…”
supporting
confidence: 80%
“…1͑b͒ a STM topographic image of single-phase c-Si: H. Here we see that the crystallites' aggregates ͑encircled by curves͒ are composed of microcrystallites with diameters of about 20 nm, in good agreement with the values we estimated from our Raman spectra. 29,30 The STM image, however, does not yield any contrast between the crystallites and the ͑possibly existing 10 ͒ disordered Si tissues. Such information, which obviously is of utmost importance for the present investigation, is provided by monitoring the phase shift in AFM tapping mode measurements, known to yield materialdependent contrast.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Teknik baru yang dikembangkan beberapa tahun terakhir ini adalah teknik Hot Wire Chemical Vapor Deposition (Hot Wire CVD), yaitu metode CVD yang dibantu dengan filamen panas [3][4][5][6][7]. Dengan teknik baru ini, Lapisan tipis yang dihasilkan mempunyai kualitas yang relatif lebih baik akibat dekomposisi silan pada permukaan filamen panas [8,9].…”
unclassified
“…In an attempt to overcome the first problem it was suggested that, along with molecular flows, atomic flows of matter be also used in gas source molecular beam epitaxy (GSMBE) set-ups, which can be generated on an additional heated element in the form of a tungsten wire [2,3] or a sublimating silicon bar [4] inserted inside the reactor. The effects of additional atomic flows on the rate of atoms incorporation in a growing Sil.,Ge, layer with the "hot wire" method were analysed in [5,6] for different versions of the GSMBE.…”
Section: Introductionmentioning
confidence: 99%